Time controlled automatic fish feeder for indoor aquarium - Ali, MA; Rahman, MM; Hasan, MN; Galib, SM (Bangladesh Journal of Scientific and Industrial Research, 2020)
The purpose of this research is about the design and implementation of an automatic feeder to feed fishes in the aquarium when their owners leave home for a prolonged time or forget to feed timely due to their busyness. The mechanical drawing of the feeder is prepared in Auto Desk Fusion 360 software which is followed by the fabrication in a 3-D printer. For automatic feeding, an Arduino microcontroller board has been integrated with the designed mechanical system to control the opening and closing of the food chamber door with the help of a servo motor. An easy digital LCD programming system allows the user to set the time interval between two successive food deliveries and the number of servo rotation at each delivery to supply their desired amount of food. The performance of this portable and the low-cost feeder has been tested which has shown the reliability to dispense the accurate amount of food. Bangladesh J. Sci. Ind. Res.55(4), 289-300, 2020